ESRA19-0312 Skin antisepsis with 2% alcoholic chlorhexidine versus povidone-iodine-alcohol for the prevention of perineural catheter colonization. (30th August 2019) - Harkouk, H; Thibault Sogorb, T; Beauchet, A; Espinasse, F; Lawrence, C; Martinez, V; Fletcher, D
Abstract : Background and aims: Multimodal analgesia including a locoregional technique using perineural catheters (PNC) is recommended to treat moderate to severe acute postoperative pain. Indwelling perineural catheters is at risk of bacterial colonization. the aim of this study is to compare the cutaneous antiseptic efficacy to prevent bacterial colonization using 2% alcoholic chlorhexidine versus povidone-iodine-alcohol for PNC in orthopaedic. Methods: This is a randomized, controlled trial comparing a skin antisepsis strategy with 2% alcoholic chlorhexidine versus povidone-iodine-alcohol for PNC indwelling prior to orthopaedic surgery. the primary endpoint was the incidence of bacterial colonization of catheters (threshold> 1000 colonies forming units/ml). Secondary endpoints were the incidence of catheter-related infections and the side effects of antiseptic solutions. a multiple regression analysis was used to evaluate the risk factors independently associated with bacterial colonization. a p value < 0.05 was considered statistically significant. Results: From November 2016 to May 2018, 113 patients were analyzed. the use of alcoholic chlorhexidine was associated with a decreased incidence of catheters' colonization (OR: 0.28 [0.09–0.75], p = 0.01). There were no cases of catheter-related infection or adverse effects related to antiseptic solutions in either group. the risk factors associated with colonization were the duration of catheter use ≥ 3 days (p = 0.02) and obesity (p = 0.005). the most frequently bacteria found was Staphylococcus epidermidis. Conclusions: Skin disinfection using 2% alcoholic chlorhexidine improve prevention of bacterial colonization for indwelling perineural catheter.